Motivasi Investasi dan Pengetahuan Investasi: Kunci Penting dalam Mendorong Minat Investasi Mahasiswa Manajemen di Pasar Modal - Ramadan Bahu; Idham Masri Ishak; Hais Dama (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to investigate the influence of investment motivation and investment knowledge on investment interest in the capital market (a study on Management students at the Faculty of Economics and Business, Universitas Negeri Gorontalo. The sample size consists 93 studets. The sampling method employs the slovin method, and the data type is primary. Date are collected using questionnaires and surveys. The research analysis testing employs multiple regresssion analysis, then analyzed using the SPSS 16 application The results indicate that, partially, investment motovation has an effect on investment interest, as shown by the Tcount of 5.047 > 1.986. Similarly, investment knowledge also influences investment interest, with an Fcount of 39.930 > 3.10. This means that investment motivation and investment knowledge simultaneously affect student’s Interest in investing in the capital market. The R Square value in this research is 0.470, indicating that the variables investment motivation and investment knowledge explain 47% of the investment interest variable, while the remaining 53% is influenced by other variables not explained in this research.